Strategic Planning for Sustainable Tourism Development in Pariaman City - Adrisoni; Lukman, Syukri; Pujani, Vera (DINASTI RESEARCH, 2024)
This study aims to determine Strategic Planning for Sustainable Tourism Development in Pariaman City. It is noted that six informants from the government have participated in this study to help develop tourism in Pariaman City. This study was conducted qualitatively through case studies, this study uses data collection through interviews with informants who have been determined based on the needs and suitability of the problem formulation, then Formulation is carried out with the Quantitative Strategy Planning Matrix (QSPM) Strategy, then Strategy Recommendations and action results in the form of Milestones. Based on the assessment of competition between marine tourism in Pariaman City, it is assessed based on the Competitive Profile Matrix (CPM). Marine tourism that is assessed as a competitive profile is Angso Duo Island, Kasiak Island, and Tangah Island. With the results of the three marine tours, Angso Duo Island is indicated as a potential marine tourism for tourism development. Then based on the results of the QSPM Matrix analysis, a score of 5.704 was obtained, which means that from the selected alternative strategies, the most appropriate strategy to be carried out at this time is an intensive strategy (tourism penetration, tourism development, and product development) or integrative (backward integration, forward integration, and horizontal integration). In conclusion, the main focus that needs to be done in tourism development in Pariaman City is to develop tourism quality through increasing events and characteristic tourism products.